Auschwitz Photographic Project: The Horror Scene - Sánchez-Macías, Inmaculada (Clio. History and History Teaching, 2020)
The educational project Auschwitz: The Horror Scene takes place between 2017 and 2019, from its gestation to the photo exhibitions and talks-colloquium in which it has been framed. It is part of an informal teaching, in which learning is determined by everyday situations of social contact, which is not organized or managed by a specific educational strategy. It is an experience that takes place in relaxed settings, as in the case of cultural associations or city councils. The author of the photographs plays the symbol of the visitor’s gaze, who, through his camera, shows us the Auschwitz death camp, describing the feelings and sensations that could occur there in the early years of the decade of the 40.